Narrative-based autobiographical memory interventions for PTSD: a meta-analysis of randomized controlled trials - Raeder, Robert; Clayton, Nicola S.; Boeckle, Markus (Frontiers in Psychology, 2023)
This meta-analysis presents strong evidence supporting the use of NBIs in the treatment of PTSD. Clear similarities can be identified between NBIs included in this analysis that make them distinct from non-NBI interventions, which are reviewed in the discussion. Controlled comparisons between NBIs and non-NBIs would help to further understand AM mechanisms of action implicated in recovery and how various interventions facilitate them. Future research should also aim to elucidate the full range of AM impairment in individuals with PTSD to gain insight on how other memory capabilities, such as the ability to mentally simulate the future, are implicated in the pathogenesis of PTSD.